Why Are Japanese Wages So Sluggish? - Sommer, Martin (IMF Working Papers; Working Paper, 2009)
Over the past decade, productivity-adjusted wages have grown at a slower pace in Japan than in other rich countries. This paper suggests that Japan's dualities between regular and "nonregular" labor market contracts and the relatively inefficient services sector have exacerbated the negative impact of globalization and technical change on the labor income share felt in all advanced economies. Reforms aimed at increasing productivity in services and reducing gaps in employment protection and benefits between regular and nonregular workers could help put Japan's wages on an upward trajectory in the medium term.